Improved Intensive Quenching Processes for Global Mass Production - Kobasko, N. I. (European Journal of Applied Sciences, 2026)
The three principles of transient nucleate boiling are used for transition from IQ- 3 technology to IQ -2 technology to obtain the same or even better final results in hardening of machine components. That provides compressive surface residual stresses and super strengthening of materials. It is shown that cooling process in this case is extremely intensive. To provide optimal hardened layer during intensive quenching, it was developed a method for optimizing chemical composition of steel. The proposed method, patented in Ukraine, can be used to sort already existing steels in order to find suitable chemical composition that creates optimal hardened layer in hardened machine components. Cooling time should be interrupted to choose right time for bainitic transformations. Very simple and understandable for wide audience cooling time method of calculation is also proposed for recipes development. These innovations allow refusing from powerful pumps and expensive technology since similar condition of cooling, equal to IQ – 3 technologies, can be performed in already existing IQ-2 and conventional quenching tanks. It makes sense to distribute proposed innovations in the international market.